Safety and Tolerability of Lacosamide in Patients With Epilepsy: A Systematic Review and Meta-Analysis - Yang, Chunsong; Peng, Yuxuan; Zhang, Lingli; Zhao, Li (Frontiers in Pharmacology, 2021)
Background: As a third-generation antiseizure medication (ASM), Lacosamide (LCM) is recommended worldwide for patients with epilepsy. We aimed to provide more conclusive evidence for the safety and tolerability of LCM in patients with epilepsy. Methods: A systematic search was performed on MEDLINE, Embase, Cochrane Library, CBM, CNKI, IDB, VIP Database, and Wanfang Databas from inception to 2021 March and all studies assessing the safety of LCM were included. A meta-analysis was performed for safety data of LCM. Results: Eighty-three studies involving 12268 populations (11 randomized clinical trails (RCTs), 16 cohort studies, 53 case series and 3 case reports) were included in our study. Meta-analysis of the total incidence of adverse events (AEs) of LCM was 38.7% (95% CI [35.1%,45.8%]; n=75 studies). Incidence of withdrawal due to AEs was 10.8% (95% CI [9.1%, 12.6%]; n=56 studies) and incidence of serious adverse events (SAEs) was 6.5% (95% CI [4.0%, 8.9%]; n=13 studies). Most AEs were in nervous system and digestive system. The most common AEs were sedation (15.8%), dizziness (15.7%), fatigue (9.4%), and nausea/vomiting (9.3%). For children, the total incidence of AEs of LCM was 32.8% (95% CI [21.6%,44.0%]; n=16 studies) and the most common AEs were dizziness (8.6%), nausea/vomiting (8.6%) and somnolence (6.8%). Conclusions: Lacosamide is generally safe and well tollerate in patients with epilepsy. Common AEs were sedation, dizziness, and fatigue. It is necessary to pay more attention to the prevention and management of these AEs, and conduct more large-scale and high-quality studies to update safety data.